The Effect of Environmental Exploration VLOG Assignment Methods on Students' Biodiversity Literation Abilities - Prabowo, Sigit Ari; Widiyanti, Fenny; Billah, Arif (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
The purpose of this study was to determine the effect of the VLOG Environmental Exploration assignment method on students' biodiversity literacy. VLOG Environmental Exploration as a form of project assignment for students to learn to analyze the environment through independent video making. The research method used is True Experimental Design in the form of Posttest Only Control Design. The research subjects were students of IAIN Salatiga Tadris IPA in the odd semester of the 2020/2021 academic year. Data on students' biodiversity literacy abilities were obtained using tests, then analyzed by statistical difference test t-test. The results showed a significant difference in the biodiversity literacy abilities of students in the experimental class and the control class. These results indicate that VLOG Environmental Exploration can affect the increase in student biodiversity literacy. VLOG Environmental Exploration involves in-depth analysis of the condition of biodiversity in the environment in which students live. Students' cognitive abilities have an important role to play in analyzing environmental biodiversity.